Adsorption performance toward organic pollutants, odour control and anti-microbial activities of one Ag-based coordination polymer. Issue 4 (August 2018) - Liu, Ang; Wang, Chang-Zheng; Chu, Chun; Chu, Hong-Yu; Chen, Xi; Du, Ao-Fei; Mao, Jing; Zheng, Weiwei; Wang, Chong-Chen
Graphical abstract: Coordination polymer [Ag2 (idca)(H2 O)2 ] (BUC-16 ) exhibited excellent and long-term antimicrobial and alga-inhibiting (odour control) activities and biocompatibility. Abstract: A silver-based coordination polymer [Ag2 (idca)(H2 O)2 ] (BUC‑16 ), had been successfully prepared and used as efficient adsorbent to perform adsorption toward organic pollutants like promethazine hydrochlorine (PMH, 1395 mg g −1 ), sulfamethoxazole (SMX, 675 mg g −1 ), methylene blue (MB, 1317 mg g −1 ) in simulated wastewater. The slow-release of Ag + ions fromBUC-16 leads to its efficient and long-term antimicrobial and alga-inhibiting (odour control) activities. This is the first study on alga-inhibiting properties of coordination polymer, to the best of our knowledge. In vitro cytotoxicity (NIH-3T3 cells) test showed thatBUC-16 has lower cell toxicity, implying its good biocompatibility.